Solvent-free manufacture of methacrylate polymers from biomass pyrolysis products. Issue 2 (15th December 2020) - Ryan, J.; Elsmore, M. T.; Binner, E. R.; De Focatiis, D. S. A.; Irvine, D. J.; Robinson, J. P.
Abstract : Biomass pyrolysis liquid is functionalised into a potential replacement for petrochemical derived methacrylates used in resins, adhesives and binders. Abstract : This work demonstrates a novel approach to add value to pyrolysis liquids by exploiting the diverse range of alcohol functional groups present within the mixture to yield a non-energy product, without requiring extensive separation. It is shown that 79.2% of the alcohol functional groups can be converted by esterification and subsequently polymerised (85.7%) to produce a range of polymer products with peak molecular weight ( M p ) ranging from 22.9–36.9 kDa. Thermal and rheological properties of the most promising pyrolysis material have been compared with conventional poly(butyl methacrylate) (pBMA) of similar molecular weight, showing viability as a potential replacement owing to similarities in its thermorheological behaviour. A low molecular weight wax component of the novel polymer has been identified as a possible plasticizing agent, causing some decreases in viscosity. Production of the monomer is achieved in one reaction step and without separation or the use of toxic reagents. The overall mass balance and relevance to a biorefinery process is highlighted and strategies to tune the process to vary glass transition temperature ( T g ) and M p are discussed.